Influence of element discretization types to fatigue behaviors in finite element analysis. (2022) - Bintoro, Sefrian Rizki; Prabowo, Aditya Rio; Triyono,; Muhayat, Nurul
Abstract: Fatigue in materials is an event of material failure after experiencing repeated loads/cycles which are below the ultimate load/tensile strength or yield stress. The failure begins with crack initiation, where small cracks are formed at several points experiencing high-stress concentrations, and the cracks propagate along with the load that occurs until the material is no longer able to withstand the load and fractures. Currently, there are many methods to predict the failure of a material due to fatigue loads. One method that is widely used is to perform simulations on the structure. In this article, an object plate with holes made of aluminum material is simulated with 3 mesh variations, namely refinement and face sizing with mesh size 1 and 3; relevance center is fine, medium, coarse mesh using Goodman mean stress theory to determine the fatigue life and safety factor. The simulation results obtained the maximum and minimum values for deformation, equivalent stress, fatigue life, and safety factor for each variation. The mesh convergence test results are also carried out to determine the recommended mesh size based on the simulation results. From the simulation, the maximum and minimum values for total deformation, equivalent stress, and safety factor, there are differences between fine, medium, coarse, and mesh sizes and mesh types. The increase and decrease of values are not linear with mesh size. Therefore, a convergence test is needed to determine the most optimal mesh size. From the convergence results, the most optimum value for the analysis of this study with the aluminum plate object is the meshing size of 5 mm–8 mm.